2021
DOI: 10.1021/acsomega.1c02059
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Temperature on ZnO/Co3O4 Nanocomposites for High Energy Storage Supercapacitors

Abstract: We developed a two-step chemical bath deposition method followed by calcination for the production of ZnO/Co 3 O 4 nanocomposites. In aqueous reactions, ZnO nanotubes were first densely grown on Ni foam, and then flat nanosheets of Co 3 O 4 developed and formed a porous film. The aspect ratio and conductivity of the Co 3 O 4 nanosheets were improved by the existence of the ZnO nanotubes, while the bath deposition from a mixture of Zn/Co precursors (one-step method) resulted in a wrinkled plate of Zn/Co oxides.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 80 publications
1
19
0
Order By: Relevance
“…The cathode materials exhibited nanosheet structures and changed their morphologies from spherical nanoflowers (cathode-1) to flat porous films as the concentration of the Co 2+ precursor increased, as reported previously for Mn oxides and Co oxides. 11 , 20 The nanosheets of cathode-3 had a mean thickness and length of ∼10 and 197 nm, respectively, and interconnected with each other. The thickness and length of the nanosheets increased and decreased (to ∼22 and 87 nm), respectively, as the precursor concentration of Co 2+ increased to 120 mM (cathode-4); that is, the network density of the metal oxides increased.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The cathode materials exhibited nanosheet structures and changed their morphologies from spherical nanoflowers (cathode-1) to flat porous films as the concentration of the Co 2+ precursor increased, as reported previously for Mn oxides and Co oxides. 11 , 20 The nanosheets of cathode-3 had a mean thickness and length of ∼10 and 197 nm, respectively, and interconnected with each other. The thickness and length of the nanosheets increased and decreased (to ∼22 and 87 nm), respectively, as the precursor concentration of Co 2+ increased to 120 mM (cathode-4); that is, the network density of the metal oxides increased.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study, ZnO nanotubes were first deposited, and then secondary Co hydroxide nanoplates were hybridized. 20 In this study, the simultaneous deposition of Zn and Co hydroxide/oxide was not effective because the structure of the obtained Zn/Co oxides was not adequate for rapid ion adsorption/desorption and charge transfer. The simultaneous deposition of multiple metal ions is a simple method; however, investigations of the simultaneous deposition of complex TMOs for pseudocapacitor electrodes are rare.…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…So far, a myriad of techniques including chemical precipitation, sol–gel, hydrothermal, chemical bath deposition, spray pyrolysis, direct magnetron sputtering, and electrodeposition have been explored to develop nanostructured Co 3 O 4 materials. Among these deposition techniques, the electrodeposition method is found to be a simple, low temperature, and cost-effective technique for growing well adhered Co 3 O 4 nanostructures with desired morphological features and composition directly onto conductive substrates without the use of binders and conductive additives. Furthermore, in electrodeposition, factors such as the composition of the electrolyte, type of electrodeposition mode, and duration of the process can be regulated to achieve the desired morphology and texture, including nanoplates, nanoflowers, nanosheets, and nanotubes. ,,,, Subsequently, previous studies have reported a variation in morphological features, microstructure, and corresponding electrochemical performance of Co 3 O 4 materials when different types of cobalt precursor salts, namely, cobalt chloride, cobalt acetate, cobalt sulfate, and cobalt nitrate, are used. ,, The growth rate of Co 3 O 4 was observed to be higher when chloride was used as compared to acetate. Thus, a novel approach will be combining two different cobalt precursors with different anion sizes to control growth rate and tune morphology to achieve high specific capacitance.…”
Section: Introductionmentioning
confidence: 99%